Outcomes of a readers´ theatre program on oral reading prosody: An exploratory study in different environments - Ferrada Quezada, Natalia. (T&K Academic, 2021)
Readers’ theatre is a teaching strategy that consists of the interpretative reading of theatrical texts in which readers use their voices to give life to the characters. This strategy promotes the development of various skills related to fluency, among which there is prosody. This research aimed to check the efficacy of a reader’s theatre program on the prosody of oral reading. Eleven dyslexic students from the third and fourth grade of the primary school participated in this study, and who were distributed in two groups. To check the program effectiveness, a program evaluation method was used following the CIIP model and a pre-experimental pre-test post-test design. As a dependent variable, prosody and the prosodic characteristics were used and measured through the Prosody Assessment Scale. Findings showed a significant prosody improvement as well as the prosodic features. In addition, the results obtained by the program were similar in both groups of students. These findings suggest the readers' theatre is an effective strategy for improving the prosody of reading in schoolchildren of those ages and confirm that this strategy can be used as a part of an integral program for fluency development.
Keywords: Prosody.; Repeated Reading.; Dyslexia.; Readers’ theatre.